Aldosterone Modulates Cell Proliferation and Apoptosis in the Neonatal Rat Heart - Sohn, Hyung Joo (The Korean Academy of Medical Sciences, 2010)
In the present study, we investigated whether and how the mineralocorticoid receptor antagonist spironolactone affects cardiac growth and development through apoptosis and cell proliferation in the neonatal rat heart. Newborn rat pups were treated with spironolactone (200 mg/kg/d) for 7 days. The cell proliferation was studied by PCNA immunostaining. The treatment with spironolactone decreased proliferating myocytes by 32% (P<0.05), and reduced myocytes apoptosis by 29% (P<0.05). Immunoblot and immunohistochemistry for the expression of p38, p53, clusterin, TGF-β2, and extracellular signal-regulated kinase were performed. In the spironolactone group, p38, p53, clusterin, and TGF-β2 protein expression was significantly decreased (P<0.05). These results indicate that aldosterone inhibition in the developing rat heart induces cardiac growth impairment by decreasing proliferation and apoptosis of myocytes.